Protocolos nutricionais para novilhas Nelore criadas em sistemas a pasto - Bento, Felipe Cecconello (2024)
The objective of this study was to investigate the effect of nutritional protocols and time of year on nutritional and productive performance, as well as carcass and meat characteristics of Nellore heifers on pasture. Three nutritional protocols were evaluated: 0.30% of BW in the rearing phase and 1.0% of BW in the finishing phase; 0.40% of BW and 0.80% of BW; 0.50% of BW in both phases. Nine Nellore heifers were used to evaluate the nutritional parameters. The experiment was structured and conducted in a changeover design with three 3x3 squares, with three nutritional protocols and three periods each. To evaluate the productive performance and carcass and meat characteristics, 171 Nellore heifers were used in a completely randomized design. There was no interaction effect between the protocols and season for the intakes of dry matter (DM), organic matter (OM), digestible organic matter (DOM), crude protein (CP), indigestible neutral detergent insoluble fiber (NDFi), and NDFcp (g/kg BW). The nutritional protocols did not differ for the same variables. There was an interaction effect between the nutritional protocols and season for the intake of pasture dry matter, intake of supplement dry matter, and NDFcp (kg/day). There was no interaction effect between the protocols and season on the digestibility of CP and NDFcp. The nutritional protocols did not cause significant differences in these variables. There was an interaction effect between the nutritional protocols and season on the digestibility of DM and OM, in addition to the dietary concentration of digestible organic matter. There was no interaction effect between protocols and time on nitrogen (N) ingested, retained, absorbed, fecal N excretion, urinary N excretion, N retained/ingested, N retained/absorbed and microbial efficiency. There were interactions between protocols and times for ruminal ammoniacal N and serum urea N. There was no interaction between protocol and time for final body weight of heifers, average daily gain, total carcass gain, daily carcass gain and carcass gain per area of Nellore heifers. There was interaction between protocols and times for daily supplement intake and feed efficiency of the supplement. The nutritional protocols did not influence hot carcass weight (HCW), carcass yield, carcass length, carcass depth, front and rear cut weight, needle point, carcass pH, yield of the front, needle point and rear, loin-eye area (LEA), LEA/Live weight, LEA / HCW, rib eye width and depth, LEA depth and width ratio (RATIO), dorsal subcutaneous fat, meat pH, weight losses during cooking 0 days and 14 days of maturation and shear force 0 days. Furthermore, the protocols did not affect carcass conformation, fat finish and marbling. Thus, all nutritional protocols provide the same nutritional performance, productive performance, quantitative and qualitative characteristics in the carcass and meat. However, the 0.3/1.0 protocol promotes greater feed efficiency of the supplement in dry seasons, dry-rainy transition and rainy seasons.